2000
DOI: 10.1001/archinte.160.21.3227
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Rising Rates of Primary Liver Cancer in the United States

Abstract: Background: A recent increase in the incidence of hepatocellular carcinoma was reported in the United States. The cause of this witnessed rise remains unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
212
2
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 382 publications
(222 citation statements)
references
References 18 publications
3
212
2
5
Order By: Relevance
“…However, low tissue Fe isn't expected at tissues surrounding a tumor, as literature suggests that excessive Fe is associated with adverse effects resulted from oxidative stress induced (Reddy and Clark, 2004). As shown in hemochromatosis patients with excessive Fe load; it has an apparent correlation with hepatocellular carcinoma (El-Serag and Mason, 2000). Several epidemiological and clinical trials showed that low Fe levels could decrease cancer incidence including prostate cancer (Knekt et al, 1994;Mainous et al, 2005;Zacharski et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, low tissue Fe isn't expected at tissues surrounding a tumor, as literature suggests that excessive Fe is associated with adverse effects resulted from oxidative stress induced (Reddy and Clark, 2004). As shown in hemochromatosis patients with excessive Fe load; it has an apparent correlation with hepatocellular carcinoma (El-Serag and Mason, 2000). Several epidemiological and clinical trials showed that low Fe levels could decrease cancer incidence including prostate cancer (Knekt et al, 1994;Mainous et al, 2005;Zacharski et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The age-adjusted incidence and mortality rates of liver cancer have been increasing rapidly in the United States since the mid-1980s (Ries et al, 2006). While approximately half of this increase can be attributable to hepatitis C virus infection, a minimal or no increase has been related to hepatitis B virus and alcoholic liver disease (El-Serag and Mason, 2000;Hassan et al, 2002). Given that about half of the increase in liver cancer incidence is not related to hepatitis, the major risk factor in a significant proportion of the cases has yet to be identified.…”
mentioning
confidence: 99%
“…Coexistence of etiologies, such as HBV and HCV coinfection, HBV and aflatoxin B1, 3 or HCV and alcohol, increases the relative risk of developing HCC. 8 The molecular factors and interactions involved in hepatocarcinogenesis are still poorly understood. This is particularly true with respect to genomic mutations, as it has been difficult to identify common genetic changes in more than 20% to 30% of tumors.…”
mentioning
confidence: 99%